Grammatical constructions and representations of the smallpox plague in testimonies of qom elders - Picón, Estela Josefina (2021)
The smallpox plague is one of the fundamental themes that are addressed in Stories of the Tobas Aboriginals of the Gran Chaco as told bytheir elders (2007), by Orlando Sánchez. It is sometimes presented as something spontaneous and inaccessible; others, as a perceptible entity, capable of being controlled.From the perspective of Functional-Systemic Linguistics, the lexicon and grammar of Spanish codify the modes of referring to events in the form of structures that are nucleated around classes of verbs: the processes that are shown as self-generated are generally formulated with inacusative verbs, while those in which the will of the agents are constructed with transitive verbs. In the testimonies that the book unfolds, the transitive and the ergative perspective are combined, and both give an account of the ways of conceiving the disease and the effects it produces in the Qom community.